Water quality variation in tributaries of the Three Gorges Reservoir from 2000 to 2015. (1st May 2021) - Xiang, Rong; Wang, Lijing; Li, Hong; Tian, Zebin; Zheng, Binghui
Highlights: Water quality, hydrology and pollution were explored in TGR tributaries in 2000–2015. Hydrodynamic and pollution heterogeneity caused variation in water quality. Eutrophication and blooms occurred frequently downstream in spring. High nutrient levels in tributaries were caused by impoundment and pollution loads. Water quality was best in tributaries upstream areas during the impoundment period. Abstract: The Three Gorges Reservoir (TGR) underwent staged impoundment during 2003−2010. Periodic water impoundment included drainage (March to early June), low water level (June to August), impoundment (September to October), and high water level (November to February) periods. However, the impacts of the Three Gorges Dam (TGD) and impoundment on water quality of TGR tributaries remain poorly understood, especially in the long term and across the entire TGR drainage basin. Herein, water quality and hydrological indices of 27 tributaries, eutrophication of 38 tributaries, and pollution load of the TGR were determined during 2000–2015 to explore spatiotemporal variations in water quality. The results revealed slower flow velocity in tributaries and an extended residence time with the water level rising, and the water quality of tributaries was mainly affected by the mainstream backwater movement. Water quality was good in more than 60% of tested sites, had the best condition in the impoundment period, and it increased over time. Spatially, water quality in tributary upstream was better than in the backwater area, and worst in the tributary estuary. Among water quality indices, total nitrogen (TN) and total phosphorus (TP) were the key pollution indices, with median range of 1.619−2.739 and 0.088−0.277 mg/L, respectively. Additionally, water quality indices of TGR tributaries displayed temporal and spatial heterogeneity due to different hydrodynamic and pollution load conditions. A total of 38 tributaries displayed eutrophication, the frequency of blooms concentrated in spring and increased from the upper tributaries to the downstream area. These results expanded the theory of hydrodynamic variation and the associated evolution of the water environment after impoundment, could provide theoretical references for water quality management in river-type reservoir. Graphical abstract: Image, graphical abstract